Analysis of Online Learning Acceptance in Biology Education Students Using TAM (Technology Acceptance Model) - Mela Melati; Ismul Huda; Hasanuddin H; Cut Nurmaliah; Iswadi I (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2022)
Research to determine acceptance of online learning and the factors that influence it among biology education students using the Technology Acceptance Model (TAM) has been carried out since January-February 2021. ”The” research ”sample” ”was” determined ”by” simple ”random” sampling ”technique” with a ”total” sample ”of” 243 respondents. ”Data” were ”analyzed” descriptively ”quantitatively. ” The ”results” showed ”that” the acceptance of online learning in biology education students was in the range of the neutral category. Based on the hypothesis test, it is stated that all hypotheses in this study are accepted, the hypothesis that the variable easy to use online has a ”positive” effect on ”the” benefits of using online. The benefit ”variable” has a ”significant” positive effect on online acceptance and the convenience ”variable” has a ”positive” effect on the benefits of using online. The factors that affect online acceptance are the easy factor and the benefit factor. Of these two factors, the biggest influence on online acceptance is the benefit factor.Keywords: Technology Acceptance Model, Online Learning, Biology Education